(untitled) (Research, Society and Development, 2023)
This study aimed to investigate the possible correlation between periodontal disease and Alzheimer’s disease through an integrative literature review. An integrative bibliographic survey was carried out to investigate works that focus on Periodontal Disease and Alzheimer’s Disease, seeking original full-text articles published between 2017 and 2022 in Medline and LILACS databases. The guiding question of the study was "What is the evidence of the relationship between Periodontal Disease and Alzheimer’s Disease?" The final sample of this review consisted of 11 scientific articles selected by the previously established inclusion criteria. Based on the literature studied, it is speculated that oral health may be linked to Alzheimer’s disease. It was also observed that patients with Alzheimer’s disease present a generally unfavorable state of oral health, mainly related to the presence of dental caries and chronic periodontitis. Therefore, preventing chronic inflammatory diseases appears as a possible way to prevent the progression of Alzheimer’s disease.